Eksistensi Direktur Ma'had Dalam Meningkatkan Pendidikan Karakter Islami Di Asrama Putri Ma'had Bilal Bin Rabah Sorong - Muhammad Hadi Irawan; Jumadi; Muhammad Muzakki (Jurnal Pendidikan Agama Islam, 2025)
The existence of the director of Ma'had in improving the Islamic character of students has a fundamental role, the lack of Islamic character education causes moral degradation which has a serious impact on the social order and makes educational institutions slump and decline. The purpose of this study is to find out the efforts of the director of ma'had in improving Islamic character education and its supporting and inhibiting factors. This study uses a qualitative approach that is descriptive by using the case study method. In this study, nonprobability sampling was used. The type of sample used is purposive sampling. Data analysis techniques are in the form of observation, interviews and documentation. The data obtained and processed were analyzed using the Miles and Huberman model. The results of the study show that the existence of the director of ma'had in improving the Islamic character education of students is by conducting routine studies, exemplary and giving punishment. Supporting factors in improving Islamic character education are the cooperation between the ustadz and the director of the ma'had, the awareness in the students, the positive influence of peers, and adequate facilities and infrastructure. The inhibiting factors are the influence of the environment or negative influence of peers, the influence of gadgets, the absence of self-awareness, limited face-to-face time, busyness as a student, lack of communication between coaches and directors, and various kinds of unique characters of each student.